2016
DOI: 10.1155/2016/6980943
|View full text |Cite
|
Sign up to set email alerts
|

Structural Overview and Morphotectonic Evolution of a Strike-Slip Fault in the Zone of North Almora Thrust, Central Kumaun Himalaya, India

Abstract: The aim of the present research is to provide the base line details of the NNW-SSE trending Raintoli fault (RF) which is running parallel to the North Almora Thrust (NAT) along the Saryu valley from Seraghat-Naichun to Seri in the central sector of the Uttarakhand Himalaya, India. The RF is characterized as dextral strike slip fault and behaves as a ductile shear zone within the zone of NAT. The dextral sense of shear movement of RF is delineated by the fabric of the shear zone rocks including microscopically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The locations of abnormal values identified during the analysis were matched with the locations of thrusts, identified on a 1:50,000 geological map of Valdiya (). We applied the GLA method for the entire Kali River basin, where previous studies (Joshi et al, ; Kothyari & Pant, ; Luirei, ; Luirei et al, ; Pant, Kothyari, & Luirei, ; Pathak et al, , ; Paul et al, ) have shown the active tectonic movements. The GLA magnitude anomaly shows that the uncertainties within the Kali Basin occur at the intersections between active thrusts/faults and river courses, also to correctly detect the active uplift in the area, attributed to the increased sedimentation and increased erosional rates (Žibret & Žibret, , ).…”
Section: Methodsmentioning
confidence: 99%
“…The locations of abnormal values identified during the analysis were matched with the locations of thrusts, identified on a 1:50,000 geological map of Valdiya (). We applied the GLA method for the entire Kali River basin, where previous studies (Joshi et al, ; Kothyari & Pant, ; Luirei, ; Luirei et al, ; Pant, Kothyari, & Luirei, ; Pathak et al, , ; Paul et al, ) have shown the active tectonic movements. The GLA magnitude anomaly shows that the uncertainties within the Kali Basin occur at the intersections between active thrusts/faults and river courses, also to correctly detect the active uplift in the area, attributed to the increased sedimentation and increased erosional rates (Žibret & Žibret, , ).…”
Section: Methodsmentioning
confidence: 99%
“…Fine-scale geomorphology being another proxy that connotes the effects of active tectonic activities and seismological perturbances in the surface has also been taken as one of the exploratory variables of flood susceptibility, but it has previously been ignored in flood susceptibility modeling community. Some of the geomorphic markers mapped in this area which represent effects of active tectonic activity include 1) asymmetrical meander belts (Leeder and Alexander, 1987), 2) abrupt scarp faces, 3) highly sinuous mountain fronts (Taloor et al, 2019), 4) unpaired terraces (Joshi et al, 2016), 5) unilateral migration (Latrubesse, 2015), 6) shifted fan lobes and terraces (Jolley et al, 1990), etc.…”
Section: Flood Predictorsmentioning
confidence: 99%
“…Values corroborate the field evidence suggesting that this segment of the Himalayan mountain front is tectonically active. Joshi et al (2016) studied the NNW-SSE trending dextral strike-slip fault Raintoli fault (RF) that runs parallel to the North Almora thrust (NAT) along the Saryu valley from Seraghat-Naichun to Seri in the central sector of the Kumaon Himalaya, India. Reactivation along RF with oblique-slip was observed using various geomorphic indicators.…”
Section: Kumaon Himalayamentioning
confidence: 99%